Application of Tawarruq munazzam in Malaysia / Ismail Rustam - Rustam, Ismail (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Nowadays, the development of Islamic Financial Institutions has given positive impact towards Islamic bank industry. Many new contracts have been introduced as an alternative to conventional bank products. Tawarruq munazzam or known as commodity murabahah is one of the contracts. In this study, the author has set several objectives which are to explain the concept of tawarruq munazzam, discussing the fuqaha’s opinions on this contract and explain the modus operandi of tawarruq munazzam implements in Malaysia. The study founds that tawarruq munazzam is a contract that practice by Islamic bank to provide financing towards customers. The practice of this contract is contrary to the conventional bank’s financing products. This is because the features of both contracts are different. In fact, tawarruq munazzam is a contract based on the trading transaction, meanwhile, the financing product offered by conventional banks is based on loans which containing riba. Majority of contemporary fuqaha permit the practice of tawarruq munazzam based on their ijtihad to provide maslahah among the society. Meanwhile, there are also fuqaha who prohibited this practice because it seems like a hilah to permit riba. Lastly, an Every Islamic bank in Malaysia is using a platform such as as-Sidq, London Metal Exchange, and Bursa Suq al-Sila to trade the commodity while practicing tawarruq munazzam.